Mobile Learning Simulation (MLS) for Learning Physics in Heat Transfer Concept - Indarwati, Siti Hastin Nur; Catur Wibowo, Firmanul; Sugihartono, Iwan; Arymbekov, Beken (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
This research aims to develop Mobile Learning Simulation (MLS) media that is valid for learning the concept of heat transfer. The method used in this research is the Research and Development method with the ADDIE model (Analyze, Design, Develop, Implement and Evaluate). MLS was developed to make it easier for students to learn the concept of expansion and increase their understanding of the microscopic nature of heat transfer. MLS can display six 2D simulations, namely the processes of length expansion, area expansion, volume expansion, and heat transfer by conduction, convection, and radiation. The product effectiveness test was carried out with correspondents of 35 students in one of the schools in western Indonesia, obtaining an average score of 84.3% and was in the very good category. Based on the test results, the MLS application is efficient and suitable for use as a physics learning medium in high school.